KOMIK SAINS SEBAGAI MEDIA MENGEMBANGKAN DAYA IMAJINASI DAN PENGETAHUAN TUNANETRA DI YOGYAKARTA - Sutandi, Marlina; Rejeki, Clothilde Arum Jayatri; Apri, Franciscus De Paula Bramasta Meindo; Y., Yani; Novisilta, Feronika Cici (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The blind students at three schools for the special needs that we observed had difficulty imagining objects described in the braille science books. Our idea was to facilitate learning using a set of science comics. The aim was to help the students imagine, improve their knowledge on science subject, and help the teachers and parents teach the blind students. We conducted an assessment (pre-test and post-test), used the science comics in the class, and held a seminar on our program. The result shows there was an increase of 94.44% on the learning achievement.